Incorporating spirituality and religiosity in pain management and palliative care (Archives of Clinical Psychiatry, 2007)
BACKGROUND: Pain is one of the most common physical complaints which negatively affects the patients quality of life. Patients with chronic pain are difficult and often frustrating to treat. OBJECTIVE: To describe the current strategies for approaching patients with chronic pain based on scientific literature, emphasizing measures related to spirituality and religiosity. METHOD: For the present work, authors reviewed data supporting the application of clinical procedures regarding to chronic pain and palliative care with the importance of spirituality background incorporation based on indexed Medline data. RESULTS: Many studies have demonstrated a positive association between spirituality and religiosity and improvement of chronic diseases variables and markers. CONCLUSION: As religiosity and spirituality are notoriously related to the patients clinical improvement, it is highly important that the recognition of these aspects and their incorporation in the management of patients with chronic pain be conducted by health professionals.